ELF dispositions in the classroom: rethinking ELT assessment in Brazil - Haus, Camila (Árboles y Rizomas, 2025)
When attempting ELF-oriented teaching in Brazil, one of the most difficult challenges are transforming assessment practices and policies, considering how they are founded on colonial and neoliberal orientations. Yet, it is also urgent to change them, since criteria, test formats and evaluation often serve as a parameter and guidance for teachers. Given this significant washback effect in ELT, it is necessary to envision competences and alternatives for teachers to assess language learners based on ELF-related principles. This article aims to rethink classroom assessment from a local ELF disposition, by interweaving reflections about ELT assessment and ELF made in Brasil, with discussions between two English teachers. I conclude with the idea of ELF dispositions, considering how it can represent a strategy to envision alternative ways of doing assessment in ELT.
Keywords: assessment; English; teaching; ELF; dispositions